Proactive Integrated Consultation-Liaison Psychiatry: A new service model for the psychiatric care of general hospital inpatients. - Sharpe, M; Toynbee, M; Walker, J (Elsevier, 2020)
OBJECTIVE:To describe a new service model for the psychiatric care of general hospital inpatients, called Proactive Integrated Consultation-Liaison Psychiatry ('Proactive Integrated Psychological Medicine' in the UK). METHOD:The new service model was developed especially for general hospital inpatient populations with multimorbidity, such as older medical inpatients. Its design was informed by the published literature and the clinical experience of C-L psychiatrists. It was operationalized by a process of iterative piloting. RESULTS:The rationale for the new model and the principles underpinning it are outlined. Details of how to implement it, including a service manual and associated workbook, are provided. The training of clinicians to deliver it is described. The effectiveness and cost-effectiveness of this new service model is being evaluated. Whilst we have found it feasible to deliver and well-accepted by ward teams, potential challenges to its wider implementation are discussed. CONCLUSION:Proactive Integrated Consultation-Liaison Psychiatry (PICLP) is a fusion of proactive consultation and integrated care, operationalized in a field-tested service manual. Initial experience indicates that it is feasible to deliver. Its effectiveness and cost effectiveness for older patients on acute medical wards is currently being evaluated in a large multicentre randomized controlled trial (The HOME Study).